Analisis Pengujian Tarik dan Sebaran unsur pada Pengelasan Aluminium – Mild Steel menggunakan Metode Cold Metal - Bayu Prabandono; Agnes Putri Kartika Santosa; Devinta Putri Ardani; Agus Kurniawan; Mirza Yusuf (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
The technology that has been developed in recent years is the production of fusion welded plates between two different materials, for example, steel with other materials such as aluminum. Combining the two materials, aluminum and mild steel, will undoubtedly produce a material connection with good properties, for example, in a vehicle car frame. However, these two materials have different melting points, mild steel has a high melting point, and aluminum has a low melting point in the inner layer. This research aims to determine the welding results and the microstructure between aluminum plates and mild steel. The Cold Metal Transfer (CMT) welding process provides a potential method for joining dissimilar metals. In this study, various 4 mm thick aluminum alloys (Al 1100) were joined to 4 mm thick mild steel (SPHC) by CMT welding technology. It was concluded that combining aluminum alloys with mild steel using the cold metal transfer method was feasible. The optimum process variable for welding aluminum-mild steel dimensions 250 mm × 100 mm × 4 mm can be obtained with ER70S-6 wire, ArCO2 shielding gas, wire feed speed 13 m/min, and welding speed e8 mm/s.The tensile strength of the joint first increases and then decreases as the welding current increases, the highest tensile strength can reach 73.35 MPa.